IMPLEMENTASI SOFTWARE OPEN SOURCE DALAM MEMBANGUN INTRANET SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 1 KEPAHIANG - Aspriyono, Hari; Arliando, Yode (Lembaga Penerbitan Universitas Esa Unggul, 2017)
This research was conducted to create a school intranet system that can be used to support the teaching and learning process. Data collection was conducted by observation, interview and literature study in order to get the system requirement. Problems that exist in SMK Negeri 1 Kepahiang is the absence of adequate internet connection that can be used by students or teachers to conduct information search related to teaching and learning process. In addition there is no alternative system that can be used to support teaching and learning process in lieu of the internet, such as Blog, File Sharing and CBT. In this research the authors implement open source software to build a school intranet system that contains CMS, Blog, File Sharing and Computer Based test (CBT) so that the cost is very affordable. Based on the results of system implementation and testing it can be concluded that intranet systems built using open source software can be accessed on a client-server basis, user authentication runs as expected and CMS, Blog, File Sharing and CBT applications can run well. But still requires a better server specification so that its ability to serve many users will also be better.Ã‚Â Keywords: intranet, open source, cms